Temperature And Velocity Changes Across Tube Banks In One-Directional And Bi-Directional Flow Conditions - Mohd Saat, Fatimah Al Zahrah; Hasbullah, Nurjannah; Shikh Anuar, Fadhilah; Sukri, Mohamad Firdaus; Johari, Dahlia (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
The back-and-forth movement of flow in oscillatory flow condition that can be found in blood flow, thermoacoustic energy system and ocean wave can be categorized as bi-directional flow condition and heat transfer in this flow condition is not well understood. This paper reports an experimental investigation that compares temperature and velocity values between the onedirectional (the usual flow condition) and the bi-directional flow conditions. The experiment was done using thermoacoustic’s standing wave rig with two different drivers to drive the one-directional flow and bi-directional flow conditionsin the test rig. Results, that were recorded using piezoresistive pressure sensor, type-K thermocouple and hotwire anemometer, indicate that care should be exercised when calculating heat transfer in bi-directional flow conditions as the temperature and velocity changes are different compared to the one-directional flow condition. Differences were recorded to be within the range of 77% for temperature and 59.5% for velocity, presumably due to the different behavior of forced and natural convection effect as flow conditions changed